Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species - Dupérré, Nadine; Tapia, Elicio (European Journal of Taxonomy, 2016)
The spider diversity of the family Anyphaenidae in premontane, low evergreen montane and cloud forest from the Chocó region of Ecuador is examined. A total of 287 adult specimens were collected and 19 morphospecies were identified based on male specimens. Thirteen new species are described and one new genus is proposed. Five new species are described in the genus Katissa Brescovit, 1997: Katissa kurusiki sp. nov., K. puyu sp. nov., K. tamya sp. nov., K. yaya sp. nov. and K. guyasamini sp. nov. The new genus Shuyushka gen. nov. is proposed and includes three species: Shuyushka achachay gen. et sp. nov., S. moscai gen. et sp. nov. and S. wachi gen. et sp. nov. Finally, five species are described in the genus Patrera Simon, 1903: P. hatunkiru sp. nov., P. philipi sp. nov., P. suni sp. nov., P. shida sp. nov. and P. witsu sp. nov. New records are provided for Patrera fulvastra Simon, 1903 and Josa nigrifrons Simon, 1897.